"Jocks Gone Wild": Masculinity, Sexual Bullying, and the Legal Normalization of Boys' Victimization. (30th August 2021) - Small, Jamie L
Abstract: The enactment of sexual violence is a key mechanism in the reproduction of masculinity. Yet most previous research examines the victimization of women and girls, even though men and boys do sometimes experience sexual violence. I take the case of sexual bullying on a high school athletic team to investigate the legal construction of teenaged boys' sexual victimization. I examine the police investigation and subsequent prosecution of five youths who were charged with felonies related to sexual bullying. Data are threefold: 1) audio recordings of police detective interviews with 21 witnesses; 2) in-depth interviews with three attorneys who worked on the case; and 3) media reports about the case. This is an innovative approach because there is little knowledge about the analytical logics of sex crime investigations, as scholarly research often focuses on legal outcomes. Findings show that key actors involved in the case, including many of the boys, were ultimately able to contain the stigmatizing threat of male-male sexual bullying by invoking a discourse of comedy and friendship. This research has theoretical implications for masculinity studies, sociology of law, and scholarship on sexual assault.